Association of Peripartum Management and High Maternal Blood Loss at Cesarean Delivery for Placenta Accreta Spectrum (PAS): A Multinational Database Study. Issue 1 (March 2022) - Schwickert, A.; van Beekhuizen, H.J.; Bertholdt, C.; Fox, K.A.; Kayem, G.; Morel, O.; Rijken, M.J.; Stefanovic, V.; Strindfors, G.; Weichert, A.; Weizsaecker, K.; Braun, T.
Abstract : ( Acta Obstet Gynecol Scand . 2021;100(suppl 1):29–40. doi: 10.1111/aogs.14103. Epub February 21, 2020) Though there has been a global decline in maternal mortality rates, the cesarean delivery (CD) rate continues to rise, resulting in an increase of placenta accreta spectrum (PAS). PAS is associated with postpartum hemorrhage (PPH) and cesarean hysterectomy, severely impacting maternal morbidity and mortality. PAS pregnancy and delivery management vary greatly between institutions. This study investigates which management and epidemiologic factors correspond with maternal outcomes, specifically high and extraordinarily high maternal blood loss during CD when PAS is present.